Characteristics of organic food consumers in urban regions of Ljubljana and Ostrava - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
The paper presents key factors influencing the organic food purchases with special emphasis on characteristics of urban consumers. Brief explanation of conventional and especially organic agriculture development is followed by the theoretical and methodological starting point of research. Based on two case study areas (Ljubljana, Slovenia and Ostrava, Czech Republic), the survey focused on urban consumers. It was possible to analyze socio-economic characteristics of customers, reasons for purchase and purchase habits regarding organic food.
Keywords: ekološko kmetije; ekološko kmetijstvo; hrana; Ljubljana; Ostrava; preskrbovalne verige